Isolation and Cytotoxic Activity of The β-Carotene Combination of Trigona Honey and Namnam Leaves Extract (Cynometra cauliflora) - Ahmad Fathoni; La Ode Sumarlin; Fuady Hanief; Dede Sukandar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Abstract: Isolation and cytotoxic activity of the β-carotene combination of Trigona honey and Namnam leaves extract (Cynometra cauliflora) were conducted. The urgency of isolating β-carotene compounds because of their known anticancer activity. Namnam leaves are macerated using methanol, then combined with Trigona honey. Fractionation and isolation of β-carotene in combination samples were conducted out by chromatography method. The β-carotene was analyzed using UV-Vis and FTIR spectrophotometer. The cytotoxic activity test was conducted by using the Brine Shrimp Lethality Test (BSLT) method with mortality analysis using Probit Analysis with SPSS v20 and Lethal Concentration 50 (LC50) as parameters. The result showed that the cytotoxic activity of Trigona honey after combination reached 36.6% with an LC50 value of 168.2 ppm, an increase from the Trigona honey sample (LC50 = 265.2 ppm) and Namnam leaves extract (LC50 = 196.12 ppm). The highest cytotoxic activity belongs to the n-hexane fraction (LC50 = 77.6 ppm). The best eluent for β-carotene isolation is petroleum ether. There was increased cytotoxic activity in isolates (LC50 of 22.85 ppm). Isolates were analyzed by UV-Vis and FTIR and compared with standards compound. FTIR analysis results showed that the isolates had functional groups of -CH3 (v 2850-2960 cm-1), -CH3 aliphatic (v 1350-1470 cm-1), C=C (v 2100-2350 cm-1 and 675-870 cm-1), and C-O (v 1000-1300 cm-1). Thus, the combination of Trigona Honey and Namnam leaf extract can be developed as an alternative chemopreventive agent.Abstrak: Isolasi dan aktivitas sitotoksik β-karoten kombinasi madu trigona dan ekstrak daun namnam (Cynometra cauliflora) telah dilakukan. Urgensi mengisolasi senyawa β-karoten karena telah diketahui adanya aktifitas antikanker. Daun namnam dimaserasi menggunakan metanol, untuk kemudian dikombinasikan dengan madu trigona. Fraksinasi dan isolasi β-karoten pada sampel kombinasi dilakukan dengan metode kromatografi. Kandungan senyawa β-karoten dianalisis menggunakan spektrofotometer UV-Vis dan FTIR. Uji aktifitas sitotoksik dilakukan dengan metode Brine Shrimp Lethality Test (BSLT) dengan analisis mortalitas menggunakan Probit Analysis dengan software SPSS v20 dan Lethal Concentration 50 (LC50) sebagai parameter. Hasil analisis menunjukkan bahwa aktivitas sitotoksik madu trigona setelah dikombinasikan mencapai 36,6 % dengan nilai LC50 sebesar 168,2 ppm, meningkat dari sampel madu trigona dengan (LC50 = 265,2 ppm), dan ekstrak daun namnam dengan (LC50 = 196,12 ppm). Aktifitas sitotoksik tertinggi dimiliki oleh fraksi n-heksana(LC50 = 77,6 ppm). Eluen terbaik untuk isolasi β-karoten adalah petroleum eter. Terjadi peningkatan aktifitas sitotoksik pada isolat hasil pemisahan (LC50 sebesar 22,85 ppm). Isolatdianalisis dengan UV-Vis dan FTIR dan dibandingkan dengan senyawa standar. Hasil analisa FTIR menunjukkan isolat memiliki gugus fungsi -CH3 (v 2850-2960 cm-1), -CH3 alifatik (v 1350-1470 cm-1), C=C (v 2100-2350 cm-1 dan 675-870 cm-1), dan C-O (v 1000-1300 cm-1). Dengan demikian, kombinasi Madu Trigona dan ekstrak daun namnam berpotensi untuk dikembangkan sebagai agen kemoprefentif alternatif.